PENCIPTAAN BUKU NOVEL GRAPHIC PUNAKAWAN SEBAGAI UPAYA PENGENALAN WARISAN BUDAYA KEPADA ANAK-ANAK - Prayoga, Dwiki Setya; Fianto, Achmad Yanu Alif; Hidayat, Wahyu (Jurnal Art Nouveau, 2015)
Abstract: Puppet is one of the top works of art and culture of Indonesias most prominent among many other works of art. Clown character itself is essentially a manifestation of some form and the human characters have a lot of value - the value of philosophy that implies about the character and the treatment of human actions. Punakawan consists of Semar, Petruk, and Bagong Gareng. Children learn faster, more active and happy or laughing, motor skills that encourage children to be active play with entertainment, because it plays a dominant form. Lack of insight into childrens knowledge about puppetry and inedible by age in this modern era, because the preservation of cultures is increasingly lost. Because the Graphic Novel narrative, if for kids is easy to understand. Some of the above problems underlying "Graphic Novel Design Punakawan As Efforts Introduction Cultural Heritage". By using media Graphic Novel book that is easily digested, so that children will be able to easily recognize and learn the cultural values contained in the puppet characters, so that the preservation of ancestral culture can be maintained back as well as a recognition of cultural heritage.Keywords: Graphic Novel Books, Punakawan, Children, Philosophy Cheer.